Diasporic transnationalism : relocated Montserratians in the UK - Shotte, Gertrude (2007)
Maps out some principle aspects of post 1995 migration from Montserrat to the UK. Presents a brief explanation of what triggered mass migration to the UK during the last quarter of 1997. Describes the fundamental features of the post 1995 diaspora in UK and recounts the supportive relationship between the post-war, the post 1995 diaspora, and 'those who stayed behind'. Explains how pre and post 1995 migrants have managed to maintain a recognisable level of Montserratness despite being hemmed in by other dominant cultural ideologies.